An analysis of conceptions and practices of Pakistani educators in private Islamic schools in light of Iqbal's educational philosophy - Ali, Muhammad Abid (Institute of Education, International Islamic University Malaysia, 2011)
The education system for any nation is designed to realize the nation's philosophy of life and to prepare human resource for achieving its objectives. The Islamic Republic of Pakistan won its independence more than sixty-three years ago, yet its education system continues to be largely secular. Even after the mushrooming of various Islamic schools in recent years geared towards formulating an Islamic based education system, a consolidated education system to cater to the ideological nature of this country is still lacking. The purpose of this study is to qualitatively explore the conceptions of ten educators, from ten different Islamic schools across Pakistan, about the Islamic based education system and to analyze the outcomes of their efforts. Another goal is to derive the aims and objectives of education from Muhammad Iqbal's thoughts and philosophy for developing an alternative model for Islam based education, and finally to conduct an analytical study between the two. Iqbal was selected, as he is considered to be the ideologue of Pakistan and has lucidly presented his educational philosophy. The methods used in this qualitative study are interviews as the primary method, and field observations, class observations, documents review, curriculum review, and photography within the campuses as the secondary methods. Exploring Iqbal's educational thought includes drawing hermeneutical interpretations from his Persian poetical works of Asrar i khudi (Secrets of the Self), and Ramooz i bikhudi (Mysteries of Selflessness). Thematic deduction is used to draw the aims and objectives for education from Iqbal's aforementioned works. The research findings reveal that the basic thrust of efforts by the educators is towards the inculcation of Islamic values and character development in the students. The main approach is the integration of Islamic concepts into the contemporary education curriculum. There is little consideration to the compatibility aspect of the prevalent education structure with Islam's approach to education. Conflict was observed between the conceived aims and objectives and the material being used for education. All the schools strictly followed the prevalent factory model of schooling. There were no collaborated efforts among the educators for the formulation of Islam based education. However, they all agreed on the need for a model of Islamic education. Although there was unanimous agreement on the relevance of Iqbal's thoughts and philosophy to Islamic based education, the educators differed in the methodology of adopting the same. A significant discrepancy was observed between the salient features of Iqbal's educational approach and the practices of the ten educators. The results also revealed that Iqbal's concept and methodology of the development of self or individuality conformed to the approach of modern critics of contemporary education, who claim that the prevalent system is at odds with the natural human faculty of creativity. In Iqbal's educational thought, the God ordained position of His vicegerent cannot be achieved without a highly developed self; and creativity is the basic element of human self and vital for its growth.